STUDY OF LOCAL BUSINESS DEVELOPMENT BEHAVIOR IN TEMPE-BASED BUSINESS ACTORS - Lastri Fitria; Zulmahendi Zulmahendi; Cut Era Farida; Serli Darmawati; Malinda Afraini; Siti Magfirah; Marlina Wati (RADJA PUBLIKA, 2022)
MSME is a business that is capable and also plays an important role in driving the economy in Indonesia. The number of micro, small and medium enterprises (MSMEs) in Indonesia in 2019 which has been recorded by the Ministry of Cooperatives and MSEs reached 65.47 million business units. From this amount, there was an increase of 1.98% when compared to the previous years, which was 64.19 million business units. Purpose: the purpose of this study was to describe how the business behavior of tempe towards the development of tempe-based SMEs in Purwodadi Village, Kuala Pesisir District, Nagan Raya Regency. Methods: The research method used in this study is an observational method with a One Group Pretest – Posttest Design approach. Result: The percentage of business actor A before intervention was 33.3% less good as much as 66.7%, business actor B as much as 38.9%, less good as much as 61.1%. Discussion: After the intervention, the percentage of business actors A and B changed to 94.4% in the good category for business actor A and 5.6% in bad category. In business actor B the percentage is 88.9 % and less good is 11.1%.